2017
DOI: 10.4236/ce.2017.86066
|View full text |Cite
|
Sign up to set email alerts
|

Why & How We Apply PBL to Science-Gifted Education?

Abstract: This study is based upon the reflections of two teachers and fifteen students as they experience problem-based learning (PBL) for the first time. A PBL exercise was integrated into a curriculum-based Earth Science field to meet specific learning requirements of gifted students. If you give affirmative answers to all these questions, it will not be the distinctive program for the gifted children (Passow, 1982). PBL is an educational approach where a purposefully illstructured real-world problem initiates learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…As a result of their study, Adams and Callahan (1995) do not find it appropriate to use the test in diagnosing giftedness, but suggests its use in measuring scientific process skills. In literature, the use of the test is frequently encountered in studies on gifted people (Han, 2017;Kim & Kang, 2014;Robinson et al, 2014;Yang & Park, 2017). FSPS (Diet Cola Test scale), developed by Fowler (1990) and later updated by Adams and Callahan (1995), can reveal which of the scientific process steps are used effectively.…”
Section: Data Collection Tools and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of their study, Adams and Callahan (1995) do not find it appropriate to use the test in diagnosing giftedness, but suggests its use in measuring scientific process skills. In literature, the use of the test is frequently encountered in studies on gifted people (Han, 2017;Kim & Kang, 2014;Robinson et al, 2014;Yang & Park, 2017). FSPS (Diet Cola Test scale), developed by Fowler (1990) and later updated by Adams and Callahan (1995), can reveal which of the scientific process steps are used effectively.…”
Section: Data Collection Tools and Data Collectionmentioning
confidence: 99%
“…Adams ve yaptıkları çalışma sonucunda testin üstün yeteneğin tanılanmasında kullanılmasını uygun görmezken, bilimsel süreç becerilerinin ölçülmesinde kullanılmasını önermektedir. Literatürde üstün yetenekliler ile ilgili yapılan çalışmalarda testin kullanımına sıklıkla rastlanmaktadır (Han, 2017;Kim & Kang, 2014;Robinson, Dailey, Hughes & Cotabish, 2014;Yang & Park, 2017). Fowler (1990) tarafından geliştirilen ve daha sonra Adams ve Callahan (1995) tarafından güncellenen FBSB (Diet Cola Test ölçeği), bilimsel süreç basamaklarından hangilerinin etkili bir şekilde kullanılıp kullanılmadığını ortaya koyabilmektedir.…”
Section: Veri Toplama Araçları Ve Verilerin Toplanmasıunclassified
“…Even though Han pointed out in a study that PBL approach is particularly appropriate for well-gifted students because it is effective in inducing their motivations, [16] it should not be restricted to such students because it is a teaching method that leads to development of deep critical thinking in the students while stimulating the development of problem solving skills and knowledge retention [1,2]. This is reflected in the opinion of majority of the study participants who indicated that PBL is suited for all medical students and not just for extremely gifted ones.…”
Section: Discussionmentioning
confidence: 99%
“…Key elements of science programmes for high-ability students are: opportunities to experiment in a laboratory, content-based curriculum pitched at a high level, opportunities to engage with 'real' scientists, a focus on inquiry processes and authentic topics (Han 2017;Kaplan et al 2016;Van Tassel-Baska et al 2008), and the important role of NoS (Gilbert & Newberry 2007;Taber 2016). We consider these in conjunction with national policy and recommended practice alongside the data gathered from the teacher participants in this study.…”
Section: Provision For High-ability Science Studentsmentioning
confidence: 99%